2021
DOI: 10.34172/jcs.2021.015
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care Practices and Related Factors in Patients with Multiple Sclerosis (MS) Based on the Health Belief Model

Abstract: Introduction: Self-care programs can raise health in patients with Multiple Sclerosis (MS). This study aimed to identify the self-care behaviors and determinants in patients with MS according to the Health Belief Model (HBM). Methods: In this cross-sectional study, we included 280 MS patients through convenience sampling method. The collection tool was a self-administered questionnaire based on HBM. The participants were the members of MS society in Kerman, Iran. The data were analyzed using descriptive statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In the study of Habibi et al, it was also shown that the lowest score related to the constructs of the health belief model was related to the construct of perceived barriers. This study showed that there is a relationship between understanding barriers and patients' educational status, and people with lower levels of education have fewer barriers to understanding [46]. Perceived barriers to self-care are significantly related to identity, outcome, time frame and emotional representation, personal control, treatment control, and dimensions of disease coherence in perceiving illness [47].…”
Section: Discussionmentioning
confidence: 73%
“…In the study of Habibi et al, it was also shown that the lowest score related to the constructs of the health belief model was related to the construct of perceived barriers. This study showed that there is a relationship between understanding barriers and patients' educational status, and people with lower levels of education have fewer barriers to understanding [46]. Perceived barriers to self-care are significantly related to identity, outcome, time frame and emotional representation, personal control, treatment control, and dimensions of disease coherence in perceiving illness [47].…”
Section: Discussionmentioning
confidence: 73%
“…The study further signify the association between self-efficacy factors and improvement of the results of conventional MG treatment and consequently health-related quality of life. Other supporting studies conducted by Habibi, Sedighi, Jahani, Hasani and Iranpour (2021) in Iran; Wong et al (2021) in Hong Kong and Shmueli (2021) in Palestine signaled that cues to action variable is a main predictor of self-care practices and a significant driving force of uptake of a healthy behavior and interventions.…”
Section: Discussionmentioning
confidence: 94%
“…A single point was assigned for each done answer, while not done answers received no points. The total score is 15, divided in to categories; (9)(10)(11)(12)(13)(14)(15) were considered adequate and (0-8) were considered in adequate.…”
Section: ❖ Scoring Systemmentioning
confidence: 99%